Pengembangan Model Pembelajaran Motorik dengan Pendekatan Bermain Menggunakan Agility Ladder untuk Anak Sekolah Dasar - Bungsu Ulung Prakoso; Bhayu Billiandri (Paedagogie, 2026)
This research is based on the fact that the implementation of physical education learning in elementary schools has not achieved optimal results, because the learning process still tends to be oriented towards conventional approaches, resulting in low motor skill development in students. This study aims to develop a game-based motor skill learning model that utilizes agility ladders. This study used a Research and Development (R&D) approach, adopting the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. Data collection was conducted through motor skill measurements, accompanied by the use of non-test techniques, including observation, interviews, questionnaires, and documentation as supporting data. The results showed that the developed model had a high level of feasibility based on expert validation and was able to increase student engagement. However, the effectiveness test results showed an N- Gain value of 0.16, which is considered low. This finding indicates that the model has a positive impact, although its effectiveness is still limited. Therefore, this learning model has the potential to be used as an alternative in physical education learning in elementary schools, with further refinement needed.